BEYOND CONFLICT: REINTERPRETASI KONFLIK INTERNAL ISLAM DALAM PEMIKIRAN KH. BAHAUDDIN NURSALIM - Asy'ari Asy'ari (Institut Agama Islam Ngawi, 2024)
Conflict in Islam has frequently been portrayed as a destructive force that threatens social cohesion and religious harmony. Such a perspective, however, fails to account for the historical and sociological dynamics through which Islamic institutions have often evolved amid competition, contestation, and doctrinal diversity. This article explores KH. Ahmad Bahauddin Nursalim's (Gus Baha) interpretation of the social functions of conflict through the analytical framework of conflict sociology. Employing a qualitative library research design, the study examines primary data drawn from Gus Baha's public lectures alongside classical and contemporary sociological literature and scholarly works on Islam and pesantren (Islamic boarding schools). The analysis is informed by Lewis Coser's functional theory of conflict, Georg Simmel's sociology of social interaction, Everett M. Rogers' diffusion of innovations theory, and Rodney Stark and Roger Finke's religious economy theory. The findings demonstrate that conflict should not be understood solely as a source of social disintegration. Instead, under particular social and religious conditions, it may facilitate the expansion of Islamic da'wah, accelerate the diffusion of pesantren, reinforce collective solidarity, and stimulate institutional innovation. Gus Baha's perspective suggests that conflict, when guided by ethical and religious values, can become a constructive mechanism for social transformation. Accordingly, conflict in Islam should be reconceptualized as a dynamic social process that contributes to institutional resilience, religious dissemination, and the continued development of Islamic communities rather than merely as a catalyst for fragmentation.